2020
DOI: 10.1007/s42452-020-2287-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation studies of polypropylene/natural fiber composites

Abstract: Polypropylene composites were prepared using natural fibers such as pigeon pea stalk fibers and banana peel. Aerobic biodegradation studies in compost have been carried out as per ASTM with composites prepared where cellulose and polypropylene has been taken as positive and negative reference respectively. Various analytical tools like SEM, TGA, XRD, DSC and Color have been used to study the change after biodegradation in composites. Highest fiber loaded composites i.e. 40 wt% depicted highest biodegradation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…Hence, the overall crystallinity of the composites increased as burial progressed. This finding was similar to the results reported by several researchers, claiming that the crystallinity of the filled composites increased after soil burial (Yaacob et al 2016;Huang et al 2018;Luthra et al 2020).…”
Section: Dsc Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, the overall crystallinity of the composites increased as burial progressed. This finding was similar to the results reported by several researchers, claiming that the crystallinity of the filled composites increased after soil burial (Yaacob et al 2016;Huang et al 2018;Luthra et al 2020).…”
Section: Dsc Analysissupporting
confidence: 92%
“…Based on Table 2, the melting temperature (Tm) of the composites was observed in the range of 125.0 to 126.2 °C, before and after soil burial. The small changes in Tm indicated that minimal changes had been initiated by the microorganism attacks on the matrix part of the composites (Luthra et al 2020). Moreover, the crystallization temperature (Tc) and heat of fusion (H*f) for both LLDPE/PVOH composites with untreated and silane-treated kenaf increased as the soil burial test prolonged.…”
Section: Dsc Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The change in color was used as an indicator for the biodegradation of natural fiber/polymer composites. Luthra, P., Vimal, K.K., Goel, V. et al [ 56 ] suggested that the color appearance was an important parameter used in the assessing the deterioration of the PP/natural fiber composite. The color change was mainly due to the changes in the chemical structure of the lignocellulosic complex of the natural fiber in the composite.…”
Section: Resultsmentioning
confidence: 99%
“…Such biofillers also present a low cost material for fabricating biodegradable PP. While Luthra et al [106] blended PP separately with banana peel (BP) and pigeon pea stalk fibers (PS), where the fibers have been either untreated or undergone alkali or laccase enzyme treatment. In addition, MAPP was added to certain samples as coupling agents.…”
Section: Biological Degradationmentioning
confidence: 99%